More than Fun and Games: Cell 16, Female Liberation, and Physical Competence, or Why Sport Matters. Issue 17 (12th December 2019) - Schultz, Jaime
Abstract: Active in the Boston area from 1968 to 1974, members of the radical feminist organization Cell 16 advocated for a number of important causes, including martial arts training for women. In sparking the era's feminist self-defence movement, they argued that learning to fight was 'an absolutely necessary step in eradicating male supremacy and dominance'. Cell 16ers maintained that women had been conditioned to be docile, dependent, and 'pitifully weak', which not only made them easy targets for abuse, but also sustained their second-class status. More to the point, they recognized that denying girls and women opportunities in sport made them physically ineffectual. By developing 'physical competence', women could break free from the bonds that subjugated them to their subordinate roles. Theorized along the broader spectrum of physical competence, this analysis of Cell 16 offers an alternative way to think about why sport matters.